Productive performance of alternative land covers along aridity gradients: ecological, agronomic and economic perspectives - Murray, Francisco; Baldi, Germán; Bernard, Tamara von; Viglizzo, Ernesto Francisco; Jobbagy Gampel, Esteban Gabriel (2018)
The replacement of natural vegetation by pastures and extensive crops is generally driven by economic incentives and supported by technology improvements and multiple subsidies. However, towards areas of increasing aridity the productive performance of these replacements may decline from all perspectives – ecological to agronomic to economic – due to intrinsic differences in the structural and physiological adjustment of natural and cultivated vegetation to reduced and fluctuating water availability. We compare natural woody vegetation, perennial C4 pastures and annual crops (maize, soybean and wheat) along a gradient of decreasing precipitation (900–400 mm of annual mean) encompassing the current agricultural frontier of the Dry Chaco and Western Espinal ecoregions of South America. We assess (i) aboveground net primary productivity (ANPP) (ii) yields of product dry mass, edible energy and protein outputs and, (iii) economic gross profits and return of investment. We linked climatic with yield data from national statistics, field trials and empiric models, together with productive parameters and market prices obtained from local consultants and economic bulletins. Maize achieved the highest ANPP of all vegetation covers (+ 42% in average compared to the rest) along the entire precipitation gradient, while the rest of the crops were very similar to natural vegetation. Pastures approached the ANPP of natural vegetation in the humid range, but had the lowest performance below 700 mm (− 15%). Along the entire precipitation gradient, maize was outstanding in mass and edible energy yield while soybean was so in protein production. Soybean had the highest gross profit per hectare (+ 50%) and total capital return of investment (+ 70%). Pastures offered the highest functional capital return of investment (+ 98%; without fixed capital, infrastructure and land value costs), explaining their relevance at the onset of the deforestation process and the gradual prevalence of crops afterwards. While agronomic and economic incentives for natural vegetation replacement remain strong along the whole aridity gradient, crop choice rather than land use system seem to shape the key ecological process of net primary productivity.